PRESCRIPTION PATTERN OF ANTIMICROBIAL AGENTS AMONG DENTAL PRACTITIONERS IN A TERTIARY CARE CENTRE IN NORTH INDIA - Suhaib, Mohammad; Ahmad, Farida; Ahmad, Mohammed (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective:The purpose of the study was to find out the pattern of antimicrobial prescription among dental practitioners in a tertiary care centre in North India. Methods:100 prescriptions of the patients attending the various dental outpatient departments of Ziauddin Ahmed Dental College, Aligarh Muslim University were collected and tabulated between January 2016 to June 2016. An observational study was done on the obtained prescriptions on various aspects like dental pathology for which antimicrobial were prescribed, antimicrobial agents used for management of acute and chronic conditions along with their dose and duration. Compliance of the patients during therapy and adverse effects associated with the regimen was also taken into consideration and the final data was expressed as counts and percentages. Results: Out of a total of 100 patients 54 (54.0%) were males while females were numbered as 46 (42.0%) with maximum distribution of the patients between 31-40 years. On analysis the most commonly presented dental condition for which antimicrobials were prescribed were Acute/Chronic periodontitis (48%), Acute/Chronic gingivitis (32%), Caries (11%), Post RCT (4%), Pericoronitis (3%), Oral trauma (1%) and other condition (1%). For the management of above conditions antimicrobials were the most extensively used agents which were prescribed for only 3-5 days which may not be sufficient, followed by analgesics and antimicrobial mouthwashes. Among the antimicrobials used, most frequently used agents were Amoxycillin (50%) followed by Ornidazole (21%), Ofloxacin (20%), Doxycycline (16%), Cefixime (9%) and Ciprofloxacin (3%) used either alone or in combination for the management of acute and chronic conditions. Only two patients were advised for culture & sensitivity tests prior to antimicrobial therapy because of non compliance of patients. Majority (74%) of patients completed the prescribed regimen of antimicrobials while 7 patients reported adverse drug reactions(ADRs), among which most common were nausea and vomiting. Conclusions: In our study we found that the periodontal diseases were the most frequently reported conditions followed by acute/chronic gingivitis for which antimicrobials were prescribed while Amoxycillin and Ornidazole were the most commonly used antimicrobials for the management of various acute and chronic dental conditions, but were prescribed without culture & sensitivity in most cases. 7% patients reported ADRs. To conclude appropriate measures are to be promoted for rational prescribing and ADR reporting. Keywords: Amoxicillin, Dental, Antimicrobials, infections, Prescription pattern.